Analisis Hubungan Tingkat Inflasi, Kurs Rupiah, Dan Tingkat Suku Bunga Bi Rate Terhadap Indeks Harga Saham Gabungan Di Bursa Efek Indonesia (Periode Tahun 2009.4-2015.12) - ARINI, YUNITA DWI; , Dr. Didit Purnomo., M.Si (2017)
Economic analysis needs to be done in the stock analysis because there is a strong link between what's happening in the macro economic environment with the performance of a stock market. This research aims to know the influence of macro economic variables as seen from the indicators of inflation, exchange rate/exchange rate of Rupiah against the USD, and the BI Rate against the JCI in the Indonesia stock exchange years 2009.4-2015.12. This research uses a quantitative approach. Data is processed using a monthly time series data analysis with regression models. The data used are secondary data with 81 observation from April 2009-December 2015. Data collection taken with engineering documentation that is sourced from the official website of the Bank Indonesia. Analytical tools used in this research is regression by using ECM (Error Correction Model). On a classic assumption test variables in regression models have been distributed normally in the test of normality. On the test of heteroskedastisitas and autocorrelation test found no problems with the model. On the multikolonieritas test in the short term variable does not have problems, in the long run only the rate that there was no problem while inflation and BI Rate there is a problem in the model. While in the test specification model (Ramsey Reset) has the form of a linear function. Based on the analysis of the test t is well known that in the short term the exchange rate and the BI Rate turns out to give significant effects against the composite stock price index in the BEI, while inflation has no effect significantly against the composite stock price Index in BEI. In the long term, variable inflation and BI Rate turns out to give significant effects against the composite stock price index in variable-rate, while BEI does not have significant influence towards the jsx composite in BEI. ECM produces test results ECT of 0.043263, this means the ECT model already meets the criteria i.e. 0 < 0.043263 < 1, so it can be used to analyze the influence of the dependent variable against the independent variable.